Nonlinear Multimode Vibration Attenuation Using Passive Circuits - Kadri, Khaled (2024)
A Master of Science thesis in Mechanical Engineering by Khaled Kadri entitled, “Nonlinear Multimode Vibration Attenuation Using Passive Circuits”, submitted in December 2024. Thesis advisor is Dr. Samir Emam. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).